2008
DOI: 10.2215/cjn.01150308
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Kidney Disease

Abstract: In recent years, it has been demonstrated that many tissues not only express the vitamin D receptor (VDR) but also may possess 1-␣-hydroxylase and are therefore capable of the production of 1, 25-dihydroxyvitamin D, which may act locally. Such tissues include the prostate; the colon; the breast; macrophages; and cells of the vasculature, pancreas, and potentially other sites. The role of this extrarenal 1-␣-hydroxylase, with the production of 1,25-dihydroxyvitamin D in these tissues, is not well understood, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 48 publications
1
119
0
3
Order By: Relevance
“…A key renoprotective function of vitamin D is reduction of albuminuria or proteinuria, major risk factors for CKD progression, renal failure, cardiovascular events, and death. This anti-proteinuric effect and slowing the progression of DN is mediated primarily via the RAAS [50][51][52][53]. Wang and his group from the University of Chicago used the 2.5-kb human podocin gene promoter to target Flag-tagged human VDR (hVDR) to podocytes in DBA/2J mice, a genetic background known to be susceptible to diabetic renal injury.…”
Section: Vitamin D/vdrmentioning
confidence: 99%
“…A key renoprotective function of vitamin D is reduction of albuminuria or proteinuria, major risk factors for CKD progression, renal failure, cardiovascular events, and death. This anti-proteinuric effect and slowing the progression of DN is mediated primarily via the RAAS [50][51][52][53]. Wang and his group from the University of Chicago used the 2.5-kb human podocin gene promoter to target Flag-tagged human VDR (hVDR) to podocytes in DBA/2J mice, a genetic background known to be susceptible to diabetic renal injury.…”
Section: Vitamin D/vdrmentioning
confidence: 99%
“…It has been demonstrated that vitamin D supplementation has an antiproteinuric effect, 33 to regulate the reninangiotensin-aldosterone, 34 , to reduce histological changes found in glomerulosclerosis, 35 , and, finally, to reduce CKD progression. 4 To sum up even if our population with CKD is in a tropical environment, which leads to more exposure to the sun and, consequently, a higher production and serum levels of 25(OH)D, our study showed that most analyzed patients had serum levels of 25(OH)D below recommended values, especially lower among women and in patients with larger abdominal circumference. These suboptimal serum levels of vitamin D can be related to the appearance of hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 69%
“…[1][2][3][4][5][6][7] Even though little attention has been given to this association up until recently, 8,9 vitamin D deficiency is not only associated with the increased risk of osteometabolic disease, but also to other relevant clinical issues, including different types of neoplasms, [3][4][5] besides the risk of cardiovascular diseases. 10 At the same time, low levels of vitamin D have been associated with the high mortality rates in the general population and in patients who undergo hemodialysis (HD).…”
Section: Introductionmentioning
confidence: 99%
“…Low level of 25(OH)D3 has been reported in the normal populations and CKD patients (8). Low level of vitamin D3 is associated with osteoporosis, rickets, cardiovascular disorder, some autoimmune disease, multiple sclerosis, diabetes mellitus and some cancers (9).…”
Section: Discussionmentioning
confidence: 99%